Contribution of Islamic Religious Education (PAI) Teachers in Developing the Independent Character of Children with Special Needs at SLB Sukamaju, North Lampung - Hidayah, Wahyudi; Hidayah, Ridho (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Educators are individuals who show others how to achieve a better life so that their humanity improves according to their nature. The term